2013
DOI: 10.1525/sop.2013.56.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Kin Undoing and Redoing Gender: Negotiating Relational Identity among Friends and Family of Transgender Persons

Abstract: The experiences of transgender persons have gained increased attention in academic discourse; however, few studies address how significant others, family members, friends, and allies (SOFFAs) process the transition of a loved one. This study seeks to fill this gap with research based on 133 observational hours and fifty interviews. Focusing on three relational identity themes—sexual orientation, social role, and religious identity—the findings suggest that SOFFAs use various intentional and unintentional strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 59 publications
0
39
0
1
Order By: Relevance
“…Sociological research concerning transgender people is relatively limited, and the family environment in which gender transition takes place has often been overlooked (Hines, 2006;Whitley, 2013). In particular, the perspective of children with a transgender parent has been neglected (Dierckx, Motmans, Mortelmans, & T'Sjoen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sociological research concerning transgender people is relatively limited, and the family environment in which gender transition takes place has often been overlooked (Hines, 2006;Whitley, 2013). In particular, the perspective of children with a transgender parent has been neglected (Dierckx, Motmans, Mortelmans, & T'Sjoen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Theories of symbolic interaction are well known for underlying the intellectual tradition of theorizing gender as something that it is 'done', rather than something that one 'has' (West & Zimmerman, 1987). The framework is perhaps less renowned, though no less significant, for its role in research on the responses to gender transition amongst partners, family members, and friends (Whitley, 2013). Whitley's (2013) research focused on the role of reflected appraisals (relatives' perceptions of social perceptions) and stigma (relatives' experiences of negative social perceptions) amongst those with close family members and friends who are trans à .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The framework is perhaps less renowned, though no less significant, for its role in research on the responses to gender transition amongst partners, family members, and friends (Whitley, 2013). Whitley's (2013) research focused on the role of reflected appraisals (relatives' perceptions of social perceptions) and stigma (relatives' experiences of negative social perceptions) amongst those with close family members and friends who are trans à . Their study found that relatives in socially supportive environments were more able to reconfigure their ideas about gender, and so too their relationships with their trans à family member, than were those who received little social support.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…I use the term 'gatekeepers' not to imply that trans and queer people are suspicious or untrusting of their potential allies, but to establish that my friends aided me in navigating my own insecurities with a social justice issue that was one, very new to me, and two, constantly forced me to confront my own assumptions and expressions of gender. With the help of people who have gone through life-changing transitions, struggles, and successes, I overcame some of my hesitancies about rendering transgender lives authentic, and for that I am very grateful to all those who contributed to this research (see also, Whitley, 2013).…”
Section: Methodsmentioning
confidence: 99%